Analisis Penerapan Pasal Penganiayaan pada Kasus Luka Berat: Studi Putusan 53/Pid.B/2020/PN Rah - Nadhif Nur Rahmansyah (‎Fakultas Hukum Universitas Jember, 2025)
Indonesian criminal law regulates criminal acts within the Penal Code (KUHP), including assault with varying degrees of severity and intent. In Case Number 53/Pid.B/2020/PN Rah, the defendant was charged with assault causing serious injury using a machete. This thesis analyzes the appropriateness of the indictment and the judge’s consideration regarding serious injury as defined in Article 90 of the KUHP. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that the prosecutor’s indictment, which only applies Articles 351 paragraphs (2) and (1) of the KUHP, is inadequate because the defendant’s act fulfills the elements of attempted murder under Article 338 in conjunction with Article 53 of the KUHP, considering the intent to kill shown by the attack on the victim’s neck. Furthermore, the judge failed to provide sufficient justification regarding the classification of the victim’s injury as serious, as the medical report (visum et repertum) did not meet the criteria under Article 90 KUHP, and no medical expert was presented to support the decision. In conclusion, the judge’s ruling is considered flawed and should have taken into account the subsidiary charge under Article 351 paragraph (1) KUHP for simple assault. This thesis recommends that the prosecutor include the attempted murder charge as an alternative and that judges apply a stricter, more conceptual method of legal interpretation to produce more objective and fair verdicts. Keywords: Criminal Law, Assault, Serious Injury